2010
DOI: 10.1007/s10493-010-9399-z
|View full text |Cite
|
Sign up to set email alerts
|

Life history of Proctolaelaps bulbosus feeding on the coconut mite Aceria guerreronis and other possible food types occurring on coconut fruits

Abstract: Aceria guerreronis Keifer (Acari: Eriophyidae) is a major pest of coconut fruits (Cocos nucifera L.) in many countries of the Americas, Africa, and parts of Asia. Considerable attention has been given to studies of biological control agents of A. guerreronis. Proctolaelaps bulbosus Moraes, Reis and Gondim Jr. is a predator recently discovered in association with A. guerreronis. Nothing is known about its biology. The aim of this study was to determine suitable food sources for P. bulbosus, among items commonly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Other studies referred to the same predator on R. robini (Metwalli et al 1991 ), to P. bickleyi and P. bulbosus on Aceria guerreronis Keifer (Lawson-Balagbo et al 2007 andGalvão et al 2011 , respectively) and to P. yinchuanensis on Suidasia pontifi ca Oudemans (Navasero et al 2004 ). However, some Proctolaelaps species were not able to complete immature development on certain mite species, namely P. bickleyi on Steneotarsonemus furcatus De Leon or T. urticae (Lawson-Balagbo et al 2007 ), P. bulbosus on T. putrescentiae (Galvão et al 2011 ) and P. deleoni on R. robini and T. putrescenitae (Nawar 1992 ).…”
Section: Proctolaelapsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies referred to the same predator on R. robini (Metwalli et al 1991 ), to P. bickleyi and P. bulbosus on Aceria guerreronis Keifer (Lawson-Balagbo et al 2007 andGalvão et al 2011 , respectively) and to P. yinchuanensis on Suidasia pontifi ca Oudemans (Navasero et al 2004 ). However, some Proctolaelaps species were not able to complete immature development on certain mite species, namely P. bickleyi on Steneotarsonemus furcatus De Leon or T. urticae (Lawson-Balagbo et al 2007 ), P. bulbosus on T. putrescentiae (Galvão et al 2011 ) and P. deleoni on R. robini and T. putrescenitae (Nawar 1992 ).…”
Section: Proctolaelapsmentioning
confidence: 99%
“…aff. stolonifer (Galvão et al 2011 ) and P. pygmaeus as well as Proctolaelaps striatus Afi fi , Hassan and El-Bishlawy on F. oxysporum (Ibrahim et al 1989 ). However, fecundity was quite low (usually at most 10 eggs per female), except for P. bickleyi and P. bulbosus (each about 33 eggs per female), both feeding on R. aff.…”
Section: Proctolaelapsmentioning
confidence: 99%
See 1 more Smart Citation
“…The "ascoids" Proctolaelaps bickleyi (Bram) and Proctolaelaps bulbosus Moraes, Reis & Gondim Jr. have also been found associated with the coconut mite, especially on fallen fruits. Again, laboratory studies have shown the coconut mite to be an adequate food for those predators (LawsonBalagbo et al 2007, Galvão et al 2011. However, even in areas where these phytoseiids and "ascoids" are found, the coconut mite causes significant damage to coconuts (de Moraes & Flechtmann 2008), suggesting that these predators are less effective than desirable.…”
Section: Introductionmentioning
confidence: 99%
“…at 0.05 = 0.43 and 0.52 for females and males individuals, respectively. The results obtained by Galvao et al (2011) who studied the effect of different food sources included the mites Aceria guerreronis, Steneotarsonemus concavuscutum Lofego and Gondim Jr., and T. putrescentiae, the fungus Rhizopus aff. stolonifer (Ehrenb.)…”
Section: A-proctolaelaps Pygmaeusmentioning
confidence: 99%